Comparative Study of In Vitro Glycemic Index, Chemical Composition, and Organoleptic Properties of Palm Sugar (Arenga pinnata Merr.) Products - Daimon Syukri; Arif Rizkika Putra; Firdaus Firdaus; Rini Rini; Novizar Nazir; Tuty Anggraini; Muhammad Makky; Dinah Cherie (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Palm sugar (Arenga pinnata Merr.) is a natural sweetener with the potential to be developed as an alternative to white sugar due to its distinctive sensory characteristics and its reported lower glycemic index. However, quantitative data on the glycemic index of various forms of palm sugar products remain limited. This study aims to analyze the in vitro glycemic index of various palm sugar products, namely liquid sugar, molded sugar, and granulated palm sugar, and to compare them with white sugar as a reference. Additionally, the study also evaluates the chemical characteristics (moisture content and ash content) and organoleptic properties of each product. The glycemic index determination was performed using an in vitro method based on enzymatic digestion simulation and the calculation of the area under the curve (AUC) of glucose release, with glucose serving as the reference food. The results of the study indicate that all palm sugar products have a low glycemic index, namely 39 for liquid sugar, 37 for molded sugar, and 35 for granulated palm sugar, while white sugar has a moderate glycemic index of 60. The differences in glycemic index values are related to variations in sugar composition, mineral content, and the physical characteristics of each product. Organoleptic testing showed that palm sugar, particularly granulated palm sugar, received good acceptance for its color, aroma, taste, and texture. Overall, the results of this study demonstrate that palm sugar has the potential to serve as a low-glycemic index alternative sweetener, supporting the development of downstream palm sugar products and the diversification of healthier food options.